Barley Rhizosphere Microbiome Transplantation – A Strategy to Decrease Susceptibility of Barley Grown in Soils With Low Microbial Diversity to Powdery Mildew - Bziuk, Nina; Maccario, Lorrie; Sørensen, Søren J.; Schikora, Adam; Smalla, Kornelia (Frontiers in Microbiology, 2022)
Beneficial bacteria in the rhizosphere are known to trigger faster and stronger plant immune responses to biotic and abiotic stressors. In the present study, we aimed to test the hypothesis that a rhizosphere microbiome transplant may improve the immune response and reduce the disease rates of barley (Hordeum vulgare). This hypothesis was tested in a greenhouse system with the powdery mildew-causing fungus Blumeria graminis f. sp. hordei (Bgh). Detached rhizosphere microbiome from barley grown in a field soil was transplanted to barley seedlings grown in potting soil with reduced microbial diversity. Saline-treated plants served as control. At the three-leaf stage, barley was challenged with Bgh. Decreased susceptibility to Bgh was observed for barley treated with the rhizosphere microbiome transplant as displayed by lower Bgh pustule counts in a detached leaf assay. A trend towards enhanced relative transcript abundances of the defense-related genes PR1b and PR17b was observed in leaves, 24 h after Bgh challenge, when compared to the control. Moreover, 10 days after Bgh challenge, the barley rhizosphere microbiome was harvested and analyzed by sequencing of 16S rRNA gene amplicons. The microbial community composition was significantly influenced by the rhizosphere microbiome transplant and displayed higher microbial diversity compared to the control. Furthermore, microbial beta-diversity and predicted functional profiles revealed a treatment-dependent clustering. Bacterial isolates from the rhizosphere microbiome transplant showed in vitro plant beneficial traits related to induced resistance. Our results showed that transplantation of a rhizosphere microbiome could be a sustainable strategy to improve health of plants grown in potting soil with low microbial diversity under greenhouse conditions.